2011
DOI: 10.1007/s00011-011-0401-y
|View full text |Cite
|
Sign up to set email alerts
|

Severe neutrophil-mediated lung inflammation in myeloperoxidase-deficient mice exposed to zymosan

Abstract: MPO deficiency results in severe lung inflammation in mice exposed to zymosan. Relatively high MIP-2 levels likely contribute to the strong inflammatory response in these animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…This finding correlated to in vivo findings as indicated by a similar increase in the same cytokines in Mpo − / − mice following zymosan administration [72]. Similarly, it was found that Mpo − / − mice with zymosan-induced lung inflammation exhibited elevated levels of MIP-2, which correlated with increased number of neutrophils in the lung [73]. In contrast, when the TLR4 agonist LPS was used to induce acute lung inflammation, neutrophil numbers were not increased in the lung of Mpo − / − mice as was observed in WT mice [74].…”
Section: Influence Of Mpo On Cytokine Production During Lung Inflasupporting
confidence: 83%
“…This finding correlated to in vivo findings as indicated by a similar increase in the same cytokines in Mpo − / − mice following zymosan administration [72]. Similarly, it was found that Mpo − / − mice with zymosan-induced lung inflammation exhibited elevated levels of MIP-2, which correlated with increased number of neutrophils in the lung [73]. In contrast, when the TLR4 agonist LPS was used to induce acute lung inflammation, neutrophil numbers were not increased in the lung of Mpo − / − mice as was observed in WT mice [74].…”
Section: Influence Of Mpo On Cytokine Production During Lung Inflasupporting
confidence: 83%
“…As a consequence of these reactions, MPO can create an enhanced proteolytic environment that contributes to liquefaction, necrosis, and abscess formation. Severe neutrophil-mediated lung inflammation has been observed in MPO-deficient mice exposed to zymosan [95], suggesting that in that setting, MPO attenuates lung damage. Furthermore, it was demonstrated recently that MPO KO mice are defective in the oxidation and clearance of single-walled carbon nanotubes from the lungs of these animals, whereas the inflammatory response is more robust than in WT mice [96].…”
Section: Mpo Hocl Production and Neutrophil Microbicidal Activitymentioning
confidence: 99%
“…Data have been replotted from the original references. endotoxin-induced acute lung injury [95,149]. In a study comparing the susceptibility to fungal infection with WT, MPO-deficient, and CGD mice, it was concluded that when the fungal load is low, ROS formed by the NADPH oxidase of neutrophils are adequate to control infection in the absence of MPO but that at high fungal load, products of the respiratory burst and MPO are needed [144,146,150].…”
Section: Figure 5 Susceptibility Of Mpo-deficient Mice To Infectionsmentioning
confidence: 99%
“…To investigate the direct anti-inflammatory actions of tulathromycin in the absence of a bacterial stimulus, calves were challenged intratracheally with zymosan, a known Toll-like receptor 2 (TLR2) ligand that has been used as an inflammatory stimulus in vivo (31). There were no significant differences in the rectal temperatures between the groups at the time of zymosan challenge (0 h) or at 3 h and 24 h postchallenge (Table 1).…”
Section: Effects Of Tulathromycin In Calves Challenged Intratracheallmentioning
confidence: 99%